Perubahan Tutupan Lahan dan Pengaruhnya terhadap Distribusi Suhu Permukaan pada Wilayah Kota Kendari - Aris Armayanti; Hasbullah Syaf; Dewi Nurhayati Yusuf (Universitas Halu Oleo, 2020)
The phenomenon of increasing thermal in urban areas has become an important issue in recent decades and is a serious issue because it is the most important factor causing global warming and climate change. Changes in Land Cover (LC) as an effect of accelerated urbanization have a significant impact in influencing urban surface surface temperature (LST). The purpose of this study is to mapping LC changes and determine its effect on the LST distribution pattern in Kendari City. The approach in this study is to use multi-temporal Landsat-7 ETM + and Landsat-8 OLI satellite imagery data in 2001, 2014, and 2019 where the distribution of LSTs were analyzed through the thermal infrared band sensor (TIRS) and operational land imager (OLI), while the LC changes use the supervised classification method with the maximum likelihood algorithm. As a result, LC types in the study area were dominated by: mixed vegetation, tree vegetation, built-up, bare soil and water body, respectively. While LST values in various LCs from highest to lowest sequentially include: built-up area, bare soil, water body, mixed vegetation and tree vegetation.Keywords: Landsat-7, Landsat-8, LC, dan LST